MODAL MANUSIA DAN DISTRIBUSI PENDAPATAN KELUARGA - Henys Mulia (Department of Development Economics, Universitas Sriwijaya, 2006)
This study elaborates theoretically several aspects capturing the influences of human capital to parent-child's incomes. Based on Markov (chain) Model, child's income has relation to her or his parent's. However, the relationship is ambiguous. There is unclear indication whether the better-off will has rich children, or the worse-off parent will has poor child. To answer this problem, this paper uses two different intergenerational human investment models; these are Perfect Capital Market Model (but this model is rarely to apply in empirical study) and Imperfect Capital Market Model. The analysis indicates that someone's income depends mainly on his/her human capital, which the latter variable depends partly on human investment of the parent for his/her child. Notwithstanding, the two models show contextually that there are several other variables influencing parent-child's income relation. Those are parental altruism, child's ability, level of economic development, economic development system, and policies relating to human development, influencing to a parent-child human investment relation, and the magnitude of someone's income. These have effects on differenambiguity of intergenerational income relation. Keywords: human capital, distribution, income